2014
DOI: 10.3758/s13414-014-0771-7
|View full text |Cite
|
Sign up to set email alerts
|

Media multitasking and behavioral measures of sustained attention

Abstract: In a series of four studies, self-reported media multitasking (using the media multitasking index; MMI) and general sustained-attention ability, through performance on three sustained-attention tasks: the metronome response task (MRT), the sustained-attention-to-response task (SART), and a vigilance task (here, a modified version of the SART). In Study 1, we found that higher reports of media multitasking were associated with increased response variability (i.e., poor performance) on the MRT. However, in Study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
81
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(96 citation statements)
references
References 25 publications
8
81
0
7
Order By: Relevance
“…In terms of task switching, using a stimulus classification task, Ophir et al (2009) found that high media multi-taskers exhibited greater task-shift costs, despite their greater practice doing so. Similar results have been found by others (e.g., Cain & Mitroff, 2011;Sanbonmatsu, Strayer, Medeiros-Ward, & Watson, 2013; but for exceptions see Minear, Brasher, McCurdy, Lewis, & Younggren, 2013;Ralph, Thomson, Seli, Carriere, & Smilek, 2015). Recent research suggests that the deficits in task switching among high media multi-taskers may stem from smaller gray matter density in the anterior cingulate cortex (ACC), a brain region crucial for the control of attention (Loh & Kanai, 2014).…”
Section: Introductionsupporting
confidence: 57%
“…In terms of task switching, using a stimulus classification task, Ophir et al (2009) found that high media multi-taskers exhibited greater task-shift costs, despite their greater practice doing so. Similar results have been found by others (e.g., Cain & Mitroff, 2011;Sanbonmatsu, Strayer, Medeiros-Ward, & Watson, 2013; but for exceptions see Minear, Brasher, McCurdy, Lewis, & Younggren, 2013;Ralph, Thomson, Seli, Carriere, & Smilek, 2015). Recent research suggests that the deficits in task switching among high media multi-taskers may stem from smaller gray matter density in the anterior cingulate cortex (ACC), a brain region crucial for the control of attention (Loh & Kanai, 2014).…”
Section: Introductionsupporting
confidence: 57%
“…This suggests that media multitasking might have a negative impact on brain areas involved in attentional control. It is important to note, however, that an extensive follow-up study (Minear et al, 2013) failed to replicate the results of Ophir and colleagues (2009), and that a recent study failed to find evidence for a relationship between the amount of daily media multitasking activity and the ability to sustain attention (Ralph et al, 2015). These contradictory findings were the motivation for the current study.…”
Section: Accepted M Manuscriptmentioning
confidence: 65%
“…Furthermore, we extend these findings to more lifelike tasks than the more simplified ones used by Ophir et al (2009), suggesting that media multitasking may be associated with distractibility during everyday life situations as well (e.g., when trying to read in a noisy environment). Future research would benefit greatly from examining the connection between media multitasking and real-life distractibility by, for example, The fact that some previous studies have obtained contradicting results (Alzahabi and Becker, 2013;Minear et al, 2013;Ralph et al, 2015), however, means that the effects of media multitasking on attention-dependent functioning are by no means unequivocally established. It should also be noted that the effect sizes in the present study were small, but this is not surprising considering that the present study did not examine primary effects, but rather transfer effects of the amount of media multitasking to simplified attention tasks in laboratory settings.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Contrary to traditional views of multitasking, according to which attention is constantly divided, current opinion assumes rapid shifts between various sources of information (see Alzahabi & Becker, 2013, for a current study on attention in multimedia contexts; see also Ralph, Thomson, Seli, Carriere, & Smilek, 2015). Bigand et al (2000) provided several models for the processing of two melodic streams at the same time; their experimental results suggest, however, that participants did not rapidly switch between the melodies, but rather combined both streams into one perceived musical entity.…”
Section: Discussionmentioning
confidence: 86%